Omalizumab is effective in the preseasonal treatment of seasonal allergic rhinitis. Issue 1 (4th January 2022) - Zhang, Yuan; Xi, Lin; Gao, Yunbo; Huang, Yanran; Cao, Feifei; Xiong, Wei; Wang, Chengshuo; Zhang, Luo
Abstract: Background: To date no study has evaluated the efficacy of preseasonal omalizumab therapy with cost effective dose and at appropriate time point compared with standard medication in seasonal allergic rhinitis (SAR) patients. Methods: This was a prospective randomized controlled open‐label single‐centre trial. 32 SAR patients were randomized to receive a single injection of omalizumab 300‐mg approximately two weeks before start of the pollen period (PP) or medication therapy. All patients completed daily questionnaires; recording symptoms, medication use and quality of life (QoL) throughout the observation period. The primary efficacy parameter was the mean daily Combined Symptom and Medication Score (CSMS). Results: Preseasonal omalizumab significantly reduced the changes of mean daily CSMS of nose during the PP ( p < 0.001), peak pollen period (PPP) and PP after PPP (PPP‐PP) ( p = 0.002) and Post‐PP ( p = 0.009) compared to standard medication. The proportion of allergy symptoms‐relieving medication‐free days during PPP‐PP was also significantly higher in preseasonal omalizumab‐treated group (76.2(16.7‐98.8))% than in medication‐treated group (19.0(0‐71.4))% ( p = 0.030). Omalizumab could achieve the same nasal symptom control during the entire pollen season and better eye symptoms relieving results in PP ( p = 0.046) and PPP‐PP ( p = 0.004) than medication treatment. Significantly greater improvement in QoL was also obtained with omalizumab‐pretreatment during the PP ( p = 0.037) and PPP‐PP ( p = 0.004). Conclusions: Administration of a single injection of 300 mg omalizumab two weeks before start of the pollen season achieves better overall control of symptoms and QoL, with significantly reduced allergy symptoms‐relieving medication usage, compared with standard pharmacotherapy in SAR patients.